From noose to needle : capital punishment and the late liberal state - Kaufman-Osborn, Timothy V. (Timothy Vance), 1953- (Ann Arbor : University of Michigan Press, 2002)
Discusses the dilemmas of the relationship between the liberal state and capital punishment.
What is a death sentence? -- John Locke's noose -- The metaphysics of the hangman -- Silencing the voice of pain -- Womanhood unsexed on the gallows -- Needling the sovereign.
Includes bibliographical references and index.
Print version record.
English.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Capital punishment -- United States; Capital punishment -- Political aspects; Hanging -- United States; Lethal injection (Execution) -- United States; Liberalism; Free enterprise; Peine de mort -- États-Unis.; Peine de mort -- Aspect politique; Pendaison -- États-Unis.; Injection létale (Exécution capitale) -- États-Unis.; Libéralisme.; liberalism; SOCIAL SCIENCE -- Penology; HISTORY -- General; Free enterprise; Capital punishment; Capital punishment -- Political aspects; Hanging; Lethal injection (Execution); Liberalism; United States; Todesstrafe; Geschichte; USA